How Does Birth Order Affect Occupational Outcomes - Li, Yuxuan. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Economics.; Advisor: Yannis Ioannides.; Keyword: Economics.